Pengaruh Team Building Terhadap Produktivitas Kerja Karyawan di The Axana Hotel Padang - Charen Africia; Arif Adrian (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
This research is motivated by the necessity to enhance employee productivity as a means to boost customer satisfaction. One effective approach to achieve this is by focusing on and improving team building. When employees feel more comfortable, happy, and motivated, they are better able to deliver exceptional customer service. The objective of this study is to evaluasi the effect of team building on employee work productivity at The Axana Hotel Padang. This quantitative research employs a causal associative analysis approach, involving 89 employees from The Axana Hotel Padang as respondents. Regression analysis, facilitated by SPSS version 25, was used for the study. The findings reveal that team building is rated as sufficient (average score: 3.85, TCR value: 77.06%), while work productivity is considered fairly good (average score: 3.83, TCR value: 76.50%). The study also indicates a significant 60% effect of team building on employee work productivity at The Axana Hotel Padang.